VERBAL VIOLENCE IN THE DOMESTIC SPACE AND LANGUAGES OF BULLYING IN STUDENTS OF A PUBLIC EDUCATIONAL INSTITUTION IN THE DISTRICT OF AYACUCHO - GUTIÉRREZ MARTÍNEZ, Juan B. (2023)
The purpose of the work is to study the most frequent violent verbal expressions used by the students of the third grade of Secondary Education of the Mariscal Cáceres Emblematic Educational Institution, of Ayacucho, when addressing a study partner; in the same way, the aggressive phrases most used by parents in the domestic sphere. For the collection of empirical information, a survey form has been applied, where students of both sexes were asked to identify the violent languages with which they insult each other, as well as to register aggressive words expressed by their parents in situations of family violence at home. Indeed, violent languages, habitually used by students and parents, produce and reinforce social and cultural stigmas in the region and are mostly related to intellectual, physical, racial, sexual, and gender conditions.